Investment Returns Analysis of Education in East Java - Indayanti, Dwi Novi; Sugiharti, Lilik (Department of Economics, Faculty of Economics and Business, Universitas Airlangga, 2021)
Education is one of the tools in human capital investment because it is considered important in producing an adequate return to schooling. At the East Java Province in 2015 and 2018 the highest education was marked by a difference in the number of each level of education, especially at the tertiary level, which was still relatively low. So, that will be affect return to schooling received by the workforce. This research uses cross section data sourced from SAKERNAS data in 2015 and 2018, with Ordinary Least Square (OLS). The results of OLS in 2015 and 2018 shown if the level of education, age, worked training, worked experience, sex, and location have a significant effect on income. The results of the OLS regression are then used to calculated return to education based on education level, sex, and location. The results shown if the education achieved produce a rate of return that is always increasing at every level of education while return to schooling based on gender is a difference in junior and university education, in rural areas return to schooling at the primary school is higher than in the urban area. Keywords: Gender, Education, Return To Education, LocationJEL: J24, I21